INTERNAL CONTROL SYSTEM AND INFORMATION TECHNOLOGY ON THE TRANSPARENCY OF LOCAL GOVERNMENT FINANCIAL MANAGEMENT - Afrina; Rina Yuniarti; Hesti Setiorini (UPT Publikasi Ilmiah UNISBA, 2025)
Abstract. This study aims to examine the influence of the Internal Control System and Information Technology on the Transparency of Local Government Financial Management. A quantitative descriptive research method was applied to achieve this objective. The population consists of 30 Regional Apparatus Organizations (OPDs) in Mukomuko Regency, with a total sample of 100 respondents selected through purposive sampling. Primary data were collected directly from government agencies using a structured questionnaire measured on a five-point Likert scale. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 26. The results reveal that the Internal Control System does not have a significant effect on the transparency of local government financial management, as indicated by a t-value of 1.602 and a significance level of 0.112, suggesting that the hypothesis is rejected. In contrast, Information Technology demonstrates a significant positive effect on the transparency of local government financial management, with a t-value of 4.199 and a significance level of 0.000, supporting the acceptance of the hypothesis. These findings imply that while the internal control mechanisms may not independently enhance financial transparency, the adoption and effective use of information technology play a crucial role in improving accountability, accessibility, and reliability of financial information in local governance. The study contributes to the understanding of how digitalization strengthens transparency in public sector financial management, particularly in regional governments of developing countries